1987
DOI: 10.1016/0378-1135(87)90015-0
|View full text |Cite
|
Sign up to set email alerts
|

Studies on bovine breda virus

Abstract: Diarrheic feces from 21 calves were examined by electron microscopy and 16 contained particles morphologically similar to those of Breda virus. The particles were spherical or elongated, 60-270 nm in greatest dimension and had surface spikes 9-13 nm long. Convalescent serum from a human patient with Breda virus-associated diarrhea reacted with one of the bovine viruses by immune electron microscopy, suggesting a serological resemblance between human and bovine Breda-like viruses. Immune electron-microscopy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…values of positive and negative control sera among assays performed in different days. Cross-reactivity of PToV with other related viruses infecting pigs has been discarded in the three assays tested (ELISA, Western blot and virus neutralization) and these results confirm that these viruses are serologically unrelated, and are in agreement with previous results described by other authors (Woode et al, 1982(Woode et al, , 1985Lamouliatte et al, 1987). However, CPS antibodies recognized both PToV-N and BEV-N proteins (not shown), indicating that the animals used to obtain the serum had been infected by, or, exposed to PToV.…”
Section: Discussionsupporting
confidence: 89%
“…values of positive and negative control sera among assays performed in different days. Cross-reactivity of PToV with other related viruses infecting pigs has been discarded in the three assays tested (ELISA, Western blot and virus neutralization) and these results confirm that these viruses are serologically unrelated, and are in agreement with previous results described by other authors (Woode et al, 1982(Woode et al, , 1985Lamouliatte et al, 1987). However, CPS antibodies recognized both PToV-N and BEV-N proteins (not shown), indicating that the animals used to obtain the serum had been infected by, or, exposed to PToV.…”
Section: Discussionsupporting
confidence: 89%
“…So far, all attempts to grow BRV in vitro have failed (Woode et al, 1982); recent observations by Lamouliatte et al (1987) need to be confirmed. For this reason, only limited studies on the characterization of the virus (Koopmans et al, 1986 ), its diagnosis, pathology and epidemiology (Woode, 1987 ) were done.…”
Section: Introductionmentioning
confidence: 98%
“…33 These animal rotavirus strains possess a high degree of genetic homology with human strains, but animal -to -human transmission is uncommon because most animal rotaviruses are species specifi c. 34 Human toroviruses associated with gastroenteritis in immunocompromised patients serologically resembles bovine (Breda virus) 35 and equine (Berne virus) 36 toroviruses. 33 These animal rotavirus strains possess a high degree of genetic homology with human strains, but animal -to -human transmission is uncommon because most animal rotaviruses are species specifi c. 34 Human toroviruses associated with gastroenteritis in immunocompromised patients serologically resembles bovine (Breda virus) 35 and equine (Berne virus) 36 toroviruses.…”
Section: Animalmentioning
confidence: 99%